Dampak Cemaran Dioksin Bagi Keadaan Gizi Dan Kesehatan: Literature Review - Wiwin Efrizal (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Dioxins and related compounds can contaminate food and have an impact on human nutrition and health. The impact of dioxin contamination on nutrition and health is not widely known by consumers, because the effect lasts a long time after dioxin accumulates in fat tissue. This research was conducted in the form of a literature study with the aim of providing an overview of the impact of dioxin contamination on nutritional and health conditions. In research, it was found that dioxins in the body can cause free radicals which can trigger oxidation stress, so that damage to several important cellular components can occur. Consumption of foods containing antioxidants is an effort to minimize the negative effects caused by dioxin contamination in humans. Close supervision of the sources of dioxin contamination is necessary to reduce its impact on nutrition and health.